2015
DOI: 10.1590/0102-311x00168614
|View full text |Cite
|
Sign up to set email alerts
|

Estilos parentais como fator de proteção ao consumo de tabaco entre adolescentes brasileiros

Abstract: Resumo O objetivo foi analisar a associação entre o uso de tabaco (no mês e frequente) com os estilos parentais e o comportamento de fumar dos pais, em uma amostra de estudantes do Ensino Médio. Foram avaliados 17.246 estudantes do Ensino Médio de escolas públicas e privadas das 27 capitais brasileiras. A prevalência do uso de tabaco na vida foi de 25,2%, 15,3% no ano, 8,6% no mês, e 3,2% para uso frequente. Em relação aos estilos parentais, 39,2% dos pais foram classificados como negligentes, 33,3% autoritati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
2
5
0
3
Order By: Relevance
“…In this study, it was verified that the prevalence of adolescents who have already experimented with tobacco increased with age, as observed with alcohol experimentation. This significant association between tobacco experimentation and increasing age among adolescents is in agreement with several previous studies 41, [45][46][47][48] , and it was also verified that tobacco use supremacy increases worldwide with age among adolescents, especially in the range 13-15 years 49 .…”
Section: Discussionsupporting
confidence: 92%
“…In this study, it was verified that the prevalence of adolescents who have already experimented with tobacco increased with age, as observed with alcohol experimentation. This significant association between tobacco experimentation and increasing age among adolescents is in agreement with several previous studies 41, [45][46][47][48] , and it was also verified that tobacco use supremacy increases worldwide with age among adolescents, especially in the range 13-15 years 49 .…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of smoking among the studied adolescents (17.6%) was consistent with data from studies carried out with students from high school and secondary levels of the Northeast and Southeast regions of the country, with percentages corresponding to 17.5% and 15.3%, respectively (13) . A national survey with 74,589 students showed that 18.5% of respondents had smoked at least once in their lives (14) .…”
Section: Discussionsupporting
confidence: 86%
“…It is worth emphasizing that although the literature points to a trend of lower rates of cigarette smoking by adolescents in developed countries, some studies point to divergent findings such as a study conducted in an underdeveloped country (Iran) with prevalence of 4.7%; and another in a developed country such as the United States where North Carolina state recorded a prevalence of 29.7% (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) . The high rate of cigarette smoking in certain developed countries may be related to the fact that it is easier to buy cigarettes, as well as the greater difficulty in facing the economic crisis that has brought high levels of personal and family indebtedness in the face of the recession and/or economic crisis that affects several countries.…”
Section: Discussionmentioning
confidence: 99%
“…The parental relationship, social experiences and skills also contribute to the onset of tobacco use, as well as make it difficult to maintain abstinence and, therefore, make treatment difficult 25 . In general, the abstinence syndrome in women has peculiarities that manifest themselves through: irritation; emotional lability; depression; anxiety; insomnia; increased appetite and difficulty concentrating 23 .…”
Section: Discussionmentioning
confidence: 99%